Glottodidactics and its development - Skowronek, Barbara (Glottodidactica, 2014)
Glottodidactics as a scientific discipline related to the theory and practice of teaching foreign langueges in Poland. It is originated in Poland, at Adam Mickiewicz University, was created by Professor Ludwik Zabrocki, who founded an international journal Glottodidactica dealing with applied linguistics in 1966.